Airway recanalization of bronchial metastasis and obstruction by smooth muscle tumour of uncertain malignant potential by a silicone OKI‐stent™. Issue 7 (3rd June 2021) - Torii, Atsushi; Saka, Hideo; Nishimura, Rieko; Saito, Yushi; Oki, Masahide
Key message: There is no standard treatment for smooth muscle tumour of uncertain malignant potential (STUMP) but it usually has a good prognosis. Airway stenting is performed to manage central airway patency. In the present case, it was no treatment for STUMP, but performance status was good, so airway stenting was performed. Abstract : Smooth muscle tumours of uncertain malignant potential (STUMP) are rare and there is no standard treatment. We present a patient diagnosed with pulmonary metastasis of STUMP who did not respond to treatment. Airway stenting was performed to manage airway patency and improve respiratory symptoms.